Laparoscopic treatment of diffuse peritonitis for ileocolic anastomotic leak following totally laparoscopic right hemicolectomy. Issue 4 (19th October 2020) - Mari, Giulio; Achilli, Pietro; Crippa, Jacopo; Cordaro, Giuseppe; Berardi, Valter; Di Fratta, Emanuele; Maggioni, Dario
Abstract: Anastomotic leakage with local or diffuse peritonitis represents one of the severe complications that may occur after right hemicolectomy. Abdominal exploration through laparotomy is associated with an increased risk of surgical site infection, pain, incisional hernias, and prolonged recovery. Laparoscopic surgery is feasible for many emergency surgical conditions, but when it comes to a diffuse peritonitis due to an ileocolic anastomotic failure, surgical re‐intervention with a minimally invasive approach is rarely adopted. We report a case series of diffuse peritonitis caused by ile‐ocolic anastomotic failure after totally laparoscopic right hemicolectomy that were successfully managed by laparoscopic re‐interventions. In all the cases the anastomosis was resected and extracted, then peritoneal lavage with saline solution was performed and terminal ileostomy was fashioned in the right iliac fossa. Peritoneal lavage was repeated every 24 hours until the peritonitis was completely resolved. All the patients were successfully discharged after a median hospital stay of 13 days. Laparoscopic surgery for the treatment of anastomotic leak after right hemicolectomy was feasible and effective in our series of patients.